The Motivation of Learning English: A Case Study of Junior High School Students - Lestari, Khafifa Fuji; Kamariah (Universitas Nahdatul Ulama Surabaya, 2023)
This study aimed to investigate the influence of learning facilities and teaching methods on students' motivation to learn English at MTsN 3 Sidenreng Rappang South Sulawesi. Motivation is considered one of the fundamental factors in language learning success. The participants in this study were 150 students at MTsN 3 Sidenreng Rappang South Sulawesi. This research includes a type of quantitative research analysis method using descriptive statistical analysis and data analysis to test validity and reliability tests. The results of the study indicate that an improvement in learning facilities has a positive impact on enhancing students' motivation to learn English. The selection of appropriate teaching methods can create a more conducive learning environment and facilitate better understanding by students. Furthermore, the availability of good learning facilities and the implementation of suitable teaching methods can influence and strengthen students' motivation to learn. The correlation coefficient between learning facilities, teaching methods, and students' motivation to learn was examined. These findings provide strong empirical evidence of the importance of adequate learning facilities and effective teaching methods in enhancing students' motivation to learn English.